Pengaruh Kombinasi Relaksasi Benson dan Aromaterapi Lavender terhadap Fatigue pada Pasien Kanker Payudara - Emilia Septiani; Dwi Fitriyanti; Anna Jumatul Laely (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Breast cancer is when cells lose their ability to run mechanisms as they should and function normally. The global prevalence of breast cancer is 2.3 million women diagnosed with the disease. The side effects of treatment and the cancer itself often cause fatigue, one of the most common complaints of breast cancer patients. The most common management is a non-pharmacological therapy of Benson relaxation and lavender aromatherapy to manage fatigue. This quasi-experimental research determined the influence of Benson relaxation and lavender aromatherapy on fatigue in breast cancer patients with a one-group pretest-posttest approach. This study involved a total of 31 breast cancer patients, selected through a purposive sampling technique. The Wilcoxon test found a p-value of 0.014 (<0.05), indicating the effect of Benson relaxation and lavender aromatherapy collaboration toward fatigue in breast cancer patients. Nurses anticipate the application of this research to manage patients' fatigue levels, while non-pharmacological therapeutic research could potentially lower fatigue rates in other chronic diseases by incorporating new variables and extending therapy duration for a more substantial impact.